ANALYSIS OF HOW THE ADOPTION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS (UFRS) AFFECTED GLOBAL ACCOUNTING PRACTICES AND FINANCIAL REPORTING: https://doi.org/10.5281/zenodo.14744615 - Odilov, Dilshod (Journal of Contemporary World Studies, 2025)
This article looks at how using International Financial Reporting Standards (IFRS) affects accounting practices and financial reporting around the world, with a particular focus on standardising reporting methods and the effect on the quality and comparability of financial statements in different countries. By examining financial reports, accounting methods, and stakeholder views in several nations before and after the introduction of IFRS, the research shows that using IFRS has greatly improved the consistency and clarity of financial reporting, resulting in better comparability among healthcare organisations globally. Important findings suggest that healthcare organisations see greater investor trust and better access to funding, as clearer financial information helps lower the gap in knowledge. The importance of these findings could help create a stronger financial setting in healthcare, encouraging accountability and better decisions among stakeholders. Additionally, the wider effects of this research reach into policy-making, where adopting consistent accounting standards may improve regulations and support the overall stability of the global healthcare industry. This study not only highlights how IFRS changes the landscape of accounting, but also points to the essential relationship between standardised financial reporting and improved operational efficiency in healthcare, supporting ongoing alignment with international standards to promote sustainable financial practices.